Peran Guru Dalam Membimbing Ibadah Sholat Pada Anak Usia Dini Di Ra Darul Ikhlas - Nurlaili, Alya Zahro Azhari, Ria Handayani, Dhea Safira, Fennika (Ability: Journal of Education and Social Analysis, 2023)
Educators have a responsibility to instill religious values in a child to receive prayers, because it is prayer that will account for all the deeds done in the world. Teach children about the importance of prayer and what are the benefits of prayer for themselves so that children understand and absorb better to become a refraction for a child in carrying out prayers. This research was conducted to find out how the role of teachers in guiding prayer services in early childhood at RA Darul Ikhlas. This type of research uses qualitative methods and the result of this research is that in teaching prayers to children, teachers of course need to do several methods as well as: 1) Exemplary, exemplary itself is a very powerful or effective method that can be applied by teachers or parents in a teaching and learning process. 2) Habituation, this habituation method itself is a method that is carried out regularly and continuously to train children in discipline, independence, good ethics, and self-adjustment in religion 3) Good advice, good advice will make the child think well and vice versa bad advice will make the child think badly too.and so on.